(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Recently, the idea has been increasingly expressed that the student should not receive an education at all, but achieve a certain level of competence in the ways of life in human society in order to meet the social expectations of our state about becoming a new worker with the need to creatively solve complex professional problems.